Straight writes and jabs : an inside look at another year in boxing - Hauser, Thomas (University of Arkansas Press, 2013)
This book brings readers into the dressing room with elite champions in the moments before some of 2012's biggest fights. The author's award-winning investigative journalism is on display in a groundbreaking exposé of the use of performance-enhancing drugs. The book also takes a look back in time at the incomparable Archie Moore and other notable boxers.